Development of an Instrument to Assess Spirituality: Reliability and Validation of the Attitudes Related to Spirituality Scale (ARES) - Braghetta, Camilla Casaletti; Gorenstein, Clarice; Wang, Yuan Pang; Martins, Camila Bertini; Leão, Frederico Camelo; Peres, Mario Fernando Prieto; Lucchetti, Giancarlo; Vallada, Homero (Frontiers in Psychology, 2021)
Background: Several instruments that measure spirituality present overlaps with positive emotions, impacting the interpretation of their findings. In order to minimize these problems, we aimed to develop, assess the reliability and validate a new scale to evaluate spirituality. Methods: The instrument was designed using a theoretical framework minimizing tautological issues (i.e., Koenig’s framework), a qualitative study investigating the definitions of spirituality, the development of the first version of instrument by experts’ meetings and a qualitative cognitive debriefing. Then, the instrument was examined for its content validity by a multidisciplinary group of judges and was pilot-tested in two different groups - less religious (medical students – n=85) and more religious (practicing religious members – n=85). Finally, psychometric properties and validity were assessed. Results: The developed Attitudes Related to Spirituality Scale (ARES) is a self-report 11-item instrument using five-level Likert items. ARES presented appropriate psychometric properties revealing excellent internal consistency (alpha=0.98) and temporal stability (ICC=0.98). Likewise, ARES was strongly correlated with other validated R/S instruments (i.e. Duke Religion Index and Brief Multidimensional Measure of Religiousness/Spirituality) and was able to discriminate higher and lower religious groups. In the exploratory factor analysis, a unidimensional structure of the scale was described. Fit indices for the scale demonstrated good fit in the unidimensional model. Conclusion: The ARES is a reliable, valid and stable one-dimension instrument that is appropriate for use in the Portuguese-speaking population. Descriptors: Spirituality; Religion; Psychometrics.